Trade Wars and Trade Talks - Grossman, Gene M.; Helpman, Elhanan (Journal of Political Economy, 1995)
Whether governments clash in trade disputes or negotiate over trade agreements, their actions in the international arena reflect political conditions back home. Previous studies of cooperative and noncooperative trade relations have focused on governments that are immune from political pressures and that act as benevolent servants of the public interest. Here we take a first step toward introducing domestic politics into the analysis of international economic relations. We study the interactions between national leaders who are concerned both with providing a high standard of living to the general electorate and collecting campaign contributions from special interest groups. The analysis reveals the determinants of the structure of protection in a noncooperative trade war and in a cooperative trade agreement.